Modern developmental aspects in the field of economical harvesting and biodiesel production from microalgae biomass. (January 2021) - Muhammad, Gul; Alam, Md Asraful; Mofijur, M.; Jahirul, M.I.; Lv, Yongkun; Xiong, Wenlong; Ong, Hwai Chyuan; Xu, Jingliang
Abstract: Microalgae have been widely explored because of the diverse number of their worthwhile applications and potential as a source biomass for the production of biofuels and value-added materials. However, downstream techniques have yet to be fully developed to overcome techno-economic barriers. Flocculation is a superior method for harvesting microalgae from growth medium because of its harvesting efficiency, economic feasibility. Various kind of bio-flocculation harvesting methods are consider as attractive low cost and environmentally friendly options and able to harvest >90% biomass. Lipid recovery from microalgal cells is a major barrier for the biofuel industry because of process complexity and algae cell structure. Thus, the pretreatment method is necessary to disrupt the cell walls of microalgae and enhance lipid extraction. Many techniques, including dry methods of extraction, are already being implemented but found out that they are not efficient and cost-effective. Various new wet harvesting strategies have been claimed to extract major lipids in cost-efficient (30% less than conventional) way as wet technologies can eliminate the cost of cell drying and associated instruments. It is necessary to develop new methods which are energy and cost-effective, and environmentally friendlier for the commercialization of biofuels. Therefore, this review presents the advances in the progress of various flocculation harvesting methods with special emphasis on innovative bio-flocculation, the underlying mechanism of microalgae and flocculation. In this study also summarize the recent progress on microalgal oil extraction processes, and comparison was made between the processes in terms of sustainability, technology readiness, and applications in larger scales. Graphical abstract: Image 1 Highlights: Approaches of the different methods of flocculation have been outlined in depth. Bio-based flocculation methods could significantly reduce cost of microalgae harvesting. Green extraction approaches reduce time and energy for industrial viability. Judicious selection of harvesting and lipid extraction methods ensures economical biofuel production. Appropriate policy framework is required for commercialization of microalgae biofuels.